Echocardiographic reference ranges for normal left ventricular layer-specific strain: results from the EACVI NORRE study. (7th April 2020) - Tsugu, Toshimitsu; Postolache, Adriana; Dulgheru, Raluca; Sugimoto, Tadafumi; Tridetti, Julien; Nguyen Trung, Mai-Linh; Piette, Caroline; Moonen, Marie; Manganaro, Roberta; Ilardi, Federica; Chitroceanu, Alexandra Maria; Sperlongano, Simona; et al.
Abstract: Aims : To obtain the normal range for 2D echocardiographic (2DE) measurements of left ventricular (LV) layer-specific strain from a large group of healthy volunteers of both genders over a wide range of ages. Methods and results : A total of 287 (109 men, mean age: 46 ± 14 years) healthy subjects were enrolled at 22 collaborating institutions of the EACVI Normal Reference Ranges for Echocardiography (NORRE) study. Layer-specific strain was analysed from the apical two-, three-, and four-chamber views using 2DE software. The lowest values of layer-specific strain calculated as ±1.96 standard deviations from the mean were −15.0% in men and −15.6% in women for epicardial strain, −16.8% and −17.7% for mid-myocardial strain, and −18.7% and −19.9% for endocardial strain, respectively. Basal-epicardial and mid-myocardial strain decreased with age in women (epicardial; P = 0.008, mid-myocardial; P = 0.003) and correlated with age (epicardial; r = −0.20, P = 0.007, mid-myocardial; r = −0.21, P = 0.006, endocardial; r = −0.23, P = 0.002), whereas apical-epicardial, mid-myocardial strain increased with the age in women (epicardial; P = 0.006, mid-myocardial; P = 0.03) and correlated with age (epicardial; r  = 0.16, P = 0.04). End/Epi ratio at the apex was higher than at the middle and basal levels of LV in men (apex; 1.6 ± 0.2, middle; 1.2 ± 0.1, base 1.1 ± 0.1) and women (apex; 1.6 ± 0.1, middle; 1.1 ± 0.1, base 1.2 ± 0.1). Conclusion : The NORRE study provides useful 2DE reference ranges for novel indices of layer-specific strain.